Rolling resistance coefficient of various roller-ski wheel typed and manufacturers - Brulin, A.-M.; Sundström, D.; Ainegren, M. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Roller skis are used in training and competition to imitate cross-country skiing during the snow-free season, where different wheels are used for classic and skate roller skiing. Roller-ski wheels are typically categorised based on rolling resistance, with race and standard wheels commonly used in competition. The experience among athletes and coaches is that the rolling resistance coefficient (µR) of the roller-ski wheels varies not only between manufacturers but also within the same series of wheels. However, this has been sparsely investigated in previous studies [1][2]. The difference in µR can significantly influence the race performance [2]. Therefore, the aim of the study was to determine the µR of various types of roller-ski wheels from different manufacturers.